Study the Partial Molar Volume of Chrom Alum in Aqueous Poly (ethylene glycol) Solution at Different Temperature (Journal of the College of Basic Education, 2022)
This study present, the density of alum chrom in water and in aqueous solution of poly (ethylene glycol) (1500) at different temperature (288.15, 293.15, 298.15) k. Experimental values of density was used to calculate the apparent molar volume (Vθ), limiting apparent molar volume Vθ˚, experimental slope (Sv) and the partial molar volume at infinite dilution of transfer of solute Δνθ˚. These results have been interpreted the molecular interaction in term of ion- solvent, ion– ion interaction. The structure making /breaking capacities have been inferred from the sign of the second derivative of limiting partial molar volume with respect temperature at constant pressure. Alum has been formed to act as structure breaker in water and aqueous PEG solution.